Irrigtion of Gallbladder bed with bupivacaine for post- operative pain relief in laparoscopic cholecystectomy. - Al-Saad, Sabah N. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Although pain after laparoscopic cholecystectomy is less intense than after open Cholecystectomy, some patients still experience considerable discomfort, and use of local anaesthetics irrigation is controversial.Objectives :to evaluate the effect of intraperitoneal and port site instillation of local anaesthetics on pain relief in the first 6 hours postoperatively.Patient and Method: Forty patients underwent elective laparoscopic cholecystectomy were included in this study and sample was divided into two equal groups. Group A received 20 ml of 0.9% normal saline instilled in the gallbladder bed, while group B received 20 ml of 0.25% bupivacaine instilled in the same region and 10 ml of 0.5% bupivacaine in divided doses at the trocar sites. The evaluation of postoperative pain was done at fixed time interval according to the numerical rating scale,and the request time of analgesics, pain site and vital signs were recorded.Results: Pain score showed significant difference only at 0h and 1h with p-value